Parallel simulation of fully-coupled thermal-hydro-mechanical processes in CO2 leakage through fluid-driven fracture zones. (March 2015) - Huang, Zhao-Qin; Winterfeld, Philip H.; Xiong, Yi; Wu, Yu-Shu; Yao, Jun
Highlights: We developed a parallel fully-implicit THM simulator. We proposed an implicit and physical-based method to model fluid-driven fractures. The pressure response can be detected by using permanent downhole gauges. The injection rate is the major factor for fluid-driven fracturing in caprock. Our approach can be used to quantify the potential leakage pathways and leaking rates. Abstract: The safety of CO2 storage in geological formations relies on the integrity of the caprock. However, the elevated fluid pressure during CO2 injection changes the stress states in the caprock, and may lead to reactivate pre-existing fractures or even fracture the caprock. It is necessary to develop an efficient and practical monitor technology to detect and identify CO2 leakage pathways. To this end, we should understand the transport behavior of CO2 coupled with geomechanical effects during injection. In this work, we first developed an efficient parallel fully-coupled thermal-hydro-mechanical simulator to model CO2 transport in porous media. The numerical model was verified through classical problems with analytical solutions. Then, based on this simulator, we investigated the fluid flow behavior when CO2 leakage occurs through fluid-driven fracture zones. We proposed an implicit, physics-based model to simulate the fluid-driven fracturing process by using several practical correlations, including fracturing pressure functions, porosity/permeability–stress relationships. A set of numerical simulations have been conducted by considering various scenarios, such as different injection rates, locations and distributions of fracture zones, and initial fracture permeability. The results show that there are several characteristics can be used to detect CO2 leakage pathways, and it is possible to develop an advanced inverse modeling and monitoring technology to identify leakage locations, times and rates using measured pressure data of permanent downhole gauges and our simulator.